2009
DOI: 10.1096/fj.09-139527
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive bioinformatics analysis of cell‐free protein synthesis: identification of multiple protein properties that correlate with successful expression

Abstract: High-throughput cell-free protein synthesis is being used increasingly in structural/functional genomics projects. However, the factors determining expression success are poorly understood. Here, we evaluated the expression of 3066 human proteins and their domains in a bacterial cell-free system and analyzed the correlation of protein expression with 39 physicochemical and structural properties of proteins. As a result of the bioinformatics analysis performed, we determined the 18 most influential features tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 38 publications
5
29
1
Order By: Relevance
“…Overall estimation of protein expression showed that the proteins of group A represented 30.9% (460); the proteins of group C represented 52.6% (782), and the proteins of group N represented 16.5% (246) of all proteins in the dataset. Similar rates of soluble expression have been reported previously for human proteins expressed in E. coli (37) and in cell-free bacterial extracts (18).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Overall estimation of protein expression showed that the proteins of group A represented 30.9% (460); the proteins of group C represented 52.6% (782), and the proteins of group N represented 16.5% (246) of all proteins in the dataset. Similar rates of soluble expression have been reported previously for human proteins expressed in E. coli (37) and in cell-free bacterial extracts (18).…”
Section: Resultssupporting
confidence: 83%
“…In accordance with our previous results (18), the predicted presence of disulfide bonds in proteins was found to be negatively correlated with soluble protein expression and positively correlated with the insoluble expression (Fig. 2C, curves A and C).…”
Section: Ptms Whose Occurrence Negatively Correlates With Solublesupporting
confidence: 92%
See 3 more Smart Citations